The Dark Continent? : Images of Africa in European Narratives about the Congo - Andersen, Frits (Aarhus University Press, 2016)
Africa: a forgotten continent that evades all attempts at control and transcends reason. Or does it? This book describes Europes image of Africa and relates how the conception of the Dark Continent has been fabricated in European culture with the Congo as an analytical focal point. It also demonstrates that the myth was more than a creation of colonial propaganda; the Congo reform movement the first international human rights movement spread horror stories that still have repercussions today. The book cross-examines a number of witness testimonies, reports and novels, from Stanleys travelogues and Conrads 'Heart of Darkness' to Herges Tintin and Burroughs 'Tarzan', as well as recent Danish and international Congo literature. 'The Dark Continent?' proposes that the Wests attitudes to Africa regarding free trade, emergency aid and intervention are founded on the literary historical assumptions of stories and narrative forms that have evolved since 1870.